NILAI KEARIFAN LOKAL DALAM BATIK TRADISIONAL KAWUNG - Parmono, Kartini (Jurnal Filsafat "WISDOM", 2013)
Traditional batik, which was raised from local cultural roots, is rich of local wisdom that is described in "batik language". Reviewing the traditional batik is similar to reviewing values . The values of traditional batik are results of acculturation process among Javanese, Hindu, and Islamic culture added to cultural influences of immigrants. One of the traditional batik motifs/patterns is Kawung. This research shows that the traditional batik of Kawung contains values of local wisdom which are described in its patterns, colors, names, and functions. The Kawung symbolizes an ideal order of society. The Kawung gives a message that someone should be an excellent, kind, and useful person.